Power and pain in the modern prison: the society of captives revisited - Crewe, Ben; Goldsmith, Andrew John; Halsey, Mark (Clarendon studies in criminology, 2022)
'Power and Pain in the Modern Prison' discusses such matters as the pains of imprisonment, penal order, staff-prisoner relationships and the everyday world of the prison, drawing on and critiquing Sykes's theories and insights, and placing them in their historic and contemporary context.